PENGEMBANGAN SUMBER DAYA APARATUR DI ERA OTONOMI DAERAH (TELAAHAN DI PEMPROV. JATIM) - Mochammad Wispandono (Neo-Bis, 2008)
Human Resource Development is one of many aspects in human resource management that has position strategic in organization. It can be developed many manners, is like what East Java province government do it. The East Java government has one policy to development human resourece/employee.  It has known “Doing Invesment to increasing and developing human resource”. The purpose of  this policy is to develop competency employee by three aspect in human capital. Three aspect in human capital are: intellectual capital, social capital, and soft capital. Intelectual capital is knowledge and ability those own by a social collectivity, is like a organization.  In this way, the government support employee to advance study in formal education and/or sent employee to allow training course. a society includes the institutions, the relationships, the attitudes and values that govern interactions among people and contribute to economic and social development”.  Social capital is develop by interaction behind one employee and the others also desaign teamwork with stakeholders, are like University in East Java, non government organization, etc. Soft capital is develop  by increasing morality employee. It has done with briefing religion one or twice a week in mosque or church. Perhaps in this way employee is understanding how  done duties are well.